2023
DOI: 10.1002/tox.23851
|View full text |Cite
|
Sign up to set email alerts
|

Scoparone inhibits the development of hepatocellular carcinoma by modulating the p38 MAPK/Akt/NF‐κB signaling in nonalcoholic fatty liver disease mice

Abstract: Background and study aimThe mechanisms underlying the progression of non‐alcoholic fatty liver disease (NAFLD) into hepatocellular carcinoma (HCC) remains confusing and the therapeutics approaches are also challenging. Here, we aimed to investigate the effects of scoparone on the treatment of HCC stemmed from NAFLD and the underlying mechanisms.Materials and methodsA model of NAFLD‐HCC was created in mice, and these mice were treated with scoparone. Biochemical assays were conducted to assess the levels of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The most recent study showed that scoparone attenuates the pathological alterations observed in MASLD-HCC mouse models. Scoparone inhibits activation of mitogen-activated protein kinase (MAPK)/Akt signaling and reverses upregulation of NF-κB p65 and its target genes, including NF-κB, TNF-α, cyclooxygenase (COX-2), MCP-1, iNOS, and MMP-9, in MASLD-HCC models (Ye et al, 2023). These results suggest that scoparone is a potential therapeutic agent for MASLD-HCC as it inhibits MAPK/Akt/NF-κB-mediated inflammatory pathways.…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…The most recent study showed that scoparone attenuates the pathological alterations observed in MASLD-HCC mouse models. Scoparone inhibits activation of mitogen-activated protein kinase (MAPK)/Akt signaling and reverses upregulation of NF-κB p65 and its target genes, including NF-κB, TNF-α, cyclooxygenase (COX-2), MCP-1, iNOS, and MMP-9, in MASLD-HCC models (Ye et al, 2023). These results suggest that scoparone is a potential therapeutic agent for MASLD-HCC as it inhibits MAPK/Akt/NF-κB-mediated inflammatory pathways.…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%